Principle of Nonmaleficence in Islamic Jurisprudence and law and its usage in Biomedical Jurisprudence: Principle of Nonmaleficence in Islamic Jurisprudence and law - Safaei , Soheila; Abbasi , Mahmoud (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: The principle of nonmaleficence is one of the four principles of bioethics. This principle, along with other principles of bioethics has been set as a moral code and guide in the deployment of new biological technologies, especially new achievements in the medical field. The principle of nonmaleficence states that the use of new technologies should not cause injury to any person of people, human beings, and even nature and animals. This review aims to recognize this principle in the holy religion of Islam that has a very large range and a long history, which is coincided with its emergence and in the Islamic jurisprudence and law it’s called the "la-zarar act" (the rule of no harm). Materials and Methods: In this review, using the keywords of the principle of nonmaleficence, the rule of no harm, self-harm, and to ward off likely harm we searched for relevant literature in interpretations of the Holy Quran, narrative texts, juridical reference texts, and databases of Google Scholar, SID, Magiran, and NoorMags and related articles were studied. Ethical Considerations: Honesty and ethics have been observed in searching and referencing. Findings: The principle of nonmaleficence governs over humans’ all the personal and social relationships and interactions as an inclusive rule and Islam give veto power to this principle over the other laws and regulations. This principle which is also presented as an ethical principle also includes the principle of nonmaleficence determined in the bioethics of today’s global society, but it has quite a different scope and principles. Conclusion: Based on the principle of nonmaleficence in Islamic Jurisprudence and law and based on wisdom as using medical and biotechnology and testing and research, the human and mankind should not be damaged at all and even if loss or damage is probable, the caution should be made and the harm should be prevented. This principle is general and includes self-harm, too. *Corresponding Author: Soheila Safaei; Email: ssafaei_57@yahoo.com; ORCID: https://orcid.org/0000-0001-8484-0282 Please cite this article as: Safaei S. Abbasi M. Principle of Nonmaleficence in Islamic Jurisprudence and law and its usage in Biomedical Jurisprudence. Bioeth Health Law J. 2021; 1:1-7 (e19). http://doi.org/10.22037/bhl.v1i1.38174